EFFECIENCY IMPROVEMENT OF EMPLOYEE MOTIVATION IN BUDGET ORGANIZATIONS - Irina A. Tsvetochkina; Ruslan A. Baryshev (Статистика и экономика, 2016)
The importance of motivation aspects isincreasing in the modern human resourcesmanagement system. Motivation and staffincentive are the main means of ensuring theoptimal use of the enterprise resources, mobilizing workforce capacity. The article presents the results of a study to determine the types ofemployee motivation. Recommendations aregiven for the formation of an effective personnel motivation system in budget organizations.